A functionalized graphene oxide and nano-zeolitic imidazolate framework composite as a highly active and reusable catalyst for [3 + 3] formal cycloaddition reactions1. Issue 28 (28th July 2015) - Wei, Yongyi; Hao, Zhongkai; Zhang, Fang; Li, Hexing
<x xml:space="preserve">Abstract</x> A SO3H-functionalized graphene oxide and nano-ZIF-8 composite was used as an efficient catalyst for [3 + 3] formal cycloaddition reactions with pyranyl heterocycles.